Prefoldins contribute to maintaining the levels of the spliceosome LSM2–8 complex through Hsp90 in Arabidopsis. Issue 11 (12th May 2020) - Esteve-Bruna, David; Carrasco-López, Cristian; Blanco-Touriñán, Noel; Iserte, Javier; Calleja-Cabrera, Julián; Perea-Resa, Carlos; Úrbez, Cristina; Carrasco, Pedro; Yanovsky, Marcelo J; Blázquez, Miguel A; Salinas, Julio; Alabadí, David
Abstract: Although originally identified as the components of the complex aiding the cytosolic chaperonin CCT in the folding of actins and tubulins in the cytosol, prefoldins (PFDs) are emerging as novel regulators influencing gene expression in the nucleus. Work conducted mainly in yeast and animals showed that PFDs act as transcriptional regulators and participate in the nuclear proteostasis. To investigate new functions of PFDs, we performed a co-expression analysis in Arabidopsis thaliana . Results revealed co-expression between PFD and the Sm-like ( LSM ) genes, which encode the LSM2–8 spliceosome core complex, in this model organism. Here, we show that PFDs interact with and are required to maintain adequate levels of the LSM2–8 complex. Our data indicate that levels of the LSM8 protein, which defines and confers the functional specificity of the complex, are reduced in pfd mutants and in response to the Hsp90 inhibitor geldanamycin. We provide biochemical evidence showing that LSM8 is a client of Hsp90 and that PFD4 mediates the interaction between both proteins. Consistent with our results and with the role of the LSM2–8 complex in splicing through the stabilization of the U6 snRNA, pfd mutants showed reduced levels of this snRNA and altered pre-mRNA splicing patterns.